Associations Between the Macular Microvasculatures and Subclinical Atherosclerosis in Patients With Type 2 Diabetes: An Optical Coherence Tomography Angiography Study - Yoon, Jooyoung; Kang, Hyo Joo; Lee, Joo Yong; Kim, June-Gone; Yoon, Young Hee; Jung, Chang Hee; Kim, Yoon Jeon (Frontiers in Medicine, 2022)
Objective: To investigate the associations between the macular microvasculature assessed by optical coherence tomography angiography (OCTA) and subclinical atherosclerosis in patients with type 2 diabetes Methods: We included patients with type 2 diabetes who received comprehensive medical and ophthalmic evaluations including carotid ultrasonography and OCTA at a hospital-based diabetic clinic in a consecutive manner. Among them, 254 eyes with neither diabetic macular edema (DME) nor history of ophthalmic treatment from 254 patients were included. The presence of elevated carotid intima-media thickness (>1.0mm) or carotid plaque was defined as subclinical atherosclerosis. OCTA characteristics focused on foveal avascular zone (FAZ) related parameters and parafoveal vessel density (VD) were compared in terms of subclinical atherosclerosis and risk factors for subclinical atherosclerosis were identified using multivariate logistic regression analysis. Results: Subclinical atherosclerosis was observed in 148 patients (58.3%). The subclinical atherosclerosis group were older (P < 0.001), had a greater portion of patients who were male (P = 0.001) and who had hypertension (P = 0.042), had longer diabetes duration (P = 0.014), and lower VD around FAZ (P = 0.010) and parafoveal VD (all P < 0.05). In multivariate logistic regression analysis, older age (P ≤ 0.001), male sex (P ≤ 0.001), lower VD around FAZ (P = 0.043), lower parafoveal VD of both superficial capillary plexus (SCP) (P = 0.011), and deep capillary plexus (DCP) (P = 0.046) were significant factors for subclinical atherosclerosis. Conclusion: The decrease in VD around FAZ, and the VD loss in parafoveal area of both SCP and DCP were significantly associated with subclinical atherosclerosis in patients with type 2 diabetes, suggesting that common pathogenic mechanisms might predispose to diabetic micro- and macrovascular complications.